The Conformal, High‐Density SpineWrap Microelectrode Array for Focal Stimulation and Selective Muscle Recruitment - Russman, Samantha M.; Montgomery‐Walsh, Rhea; Vatsyayan, Ritwik; U, Hoi Sang; Diaz‐Aguilar, Luis D.; Chang, Eric Y.; Tang, Qingbo; Lee, Keundong; Yaksh, Tony L.; Ben‐Haim, Sharona; Ciacci, Joseph; Dayeh, Shadi A. (Advanced functional materials, 2025)
Epidural electrical stimulation (EES) of the spinal cord is widely applied for pain management and as a possible route to functional restoration after spinal cord injury. Currently, EES employs bulky, nonconformal paddle arrays with low channel counts. This limits stimulation effectiveness by requiring high stimulation currents, reduces selectivity of muscle recruitment, and requires subject‐specific designs to accommodate varied neuroanatomy across the patient population. Here, on a thin‐film, high‐channel count microelectrode array, termed SpineWrap is reported, which wraps around the dorsolateral aspect of the rat spinal cord. SpineWrap delivers focal stimulation to selectively activate muscles due to its thin substrate, high conformability, high channel count, on‐device ground, and the material properties of its platinum nanorod contacts. Through computational and in vivo studies, the SpineWrap can selectively recruit muscles in the rat lower limb and identify stimulation hotspots at a submillimeter resolution, maximizing muscle recruitment selectivity. The effect of channel count and density on muscle recruitment selectivity is also investigated and show that rat spinal cord arrays require submillimeter pitches to achieve maximal selectivity. SpineWrap represents an advancement in EES technology and, when adapted to be used chronically, has the potential to improve SCI treatment by providing more refined stimulation. This study uses a thin‐film, high channel‐count microelectrode array to deliver focal spinal cord stimulation to selectively activate lower limb muscles in rats. Both computational modeling and in vivo experiments demonstrate that this array significantly improves stimulation focality and muscle recruitment selectivity compared to traditional low channel‐count arrays.